STUDENTS' WRITING PERFORMANCE AND STRATEGIES RELATING TO THE TYPES OF WRITING ANXIETY IN INDONESIAN EFL UNIVERSITY STUDENTS - HONESTY YONANDA AYUDHIA, - (2018)
ABSTRACT Writing anxiety might cause some serious problems for the students. These problems relate to mental, physiological, and behavioral aspects which can affect the students' writing performance. This study investigates the relationship between types of students' writing anxiety and students' writing performance and also the effective strategies used by the students to overcome writing anxiety. This research used quantitative and qualitative method. As respondents, there were 50 students from English department in one university in West Sumatra. The instruments used were questionnaire followed by interview, and writing test. The results showed that most of the students experienced some physiological problems that were related to somatic anxiety. The students feel panic when they write English compositions under time constraint. It is followed by cognitive anxiety which is related to mental aspect such as have negative expectations, preoccupation with performance, and concern about other's perception. The last type is avoidance behavior in which a few students in this study tended to avoid writing. Then, the most commonly used strategy among the students was preparation strategy. The students did some preparation such as studying hard before taking a writing class or test. Chi-Square analysis found there were no association between types of writing anxiety and the students' writing performance. Pedagogical implications of this study are also presented.;---